2019
DOI: 10.1002/gj.3503
|View full text |Cite
|
Sign up to set email alerts
|

Biofacies and diagenetic alterations of the Pleistocene coral reefs, northwest Red Sea coast, Saudi Arabia

Abstract: Middle to Late Pleistocene coral reefs stretch in three discontinuously elevated units above the present sea level between Duba and Sharma along the Red Sea coast, northwest Saudi Arabia. They correspond to MIS 5, MIS 7, and MIS 9 of the deep sea cores. Each unit exhibits prominent terraces as a result of the onlap during different sea levels, erosion during transgression, and tectonic uplift. Framestones, bafflestones, bindstones, packstones, grainstones and floatstones of coral, algal, and other bioclasts ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…The boring assemblage in the present study represented several communities that formed during the formation of Late Pleistocene reef unit. Increasing water depth during transgression and eustatic fluctuations changed the shallow, well-oxygenated coral rock, back-reef, and reef crest assemblages dominated by polychaete and bivalve borings into the deep lower-energy upper reef slope community dominated by boring sponges (Bassant, 1999;Uchman et al 2002, Kahal et al 2020. The present assemblage of trace fossils was typical of the Entobia ichnofacies, as defined by Bromley and Asgaard (1993b).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The boring assemblage in the present study represented several communities that formed during the formation of Late Pleistocene reef unit. Increasing water depth during transgression and eustatic fluctuations changed the shallow, well-oxygenated coral rock, back-reef, and reef crest assemblages dominated by polychaete and bivalve borings into the deep lower-energy upper reef slope community dominated by boring sponges (Bassant, 1999;Uchman et al 2002, Kahal et al 2020. The present assemblage of trace fossils was typical of the Entobia ichnofacies, as defined by Bromley and Asgaard (1993b).…”
Section: Discussionmentioning
confidence: 67%
“…Extensive environmental, sedimentological, and faunal studies have been conducted on both coasts of the Red Sea (e.g., Anan, 1984;Ziko and El-Sorogy, 1995;Abd El-Wahab and El-Sorogy, 2003;Ostrovsky et al, 2011;Pan et al, 2011;Ziko et al, 2012;El-Sorogy et al, 2012, 2013a, 2013b, 2015El-Sorogy, 2008;2015;Ruiz-Compean et al, 2017;Alharbi et al, 2018;Kahal et al, 2018Kahal et al, , 2020Youssef et al, 2020). El-Sorogy et al (2019) identified 24 foraminiferal species, 67 corals, 79 gastropods, and 63 bivalves from the same Late Pleistocene coral reef unit in the present study area.…”
Section: Introductionmentioning
confidence: 99%
“…Spectacular modern and Pleistocene fringing coral reefs rim the Red Sea coasts [24,25]. These Pleistocene coral reefs have been the subject of many studies from different points of view [26][27][28][29][30][31][32][33] However, the Red Sea waters are experiencing increasing pollution of various PTEs, especially in the northwestern areas, due to urbanization expansion and industrial and agricultural activities [18,19,34,35]. Kahal et al [19] investigated the ecological risk assessment of PTEs in the Jazan area and reported enrichment in Cd, Cr, Cu, Ni, Sb, and Zn in the coastal sediments of the area.…”
Section: Introductionmentioning
confidence: 99%